Integration of Maqashid Syaria in Nurcholish Madjid’s Thingking about Principles for Effective Good Governance - Syamsuar, Syamsuar; Chapakia, Ahmad Omar; Hamsa, Amrizal; Amelia, Amelia (Institut Agama Islam Negeri Curup, 2024)
This research aims to integrate the concept of Maqasid Syaria with Nurcholish Madjid's framework of good governance. There exists a conceptual gap that requires deeper understanding, as Nurcholish Madjid's theories on good governance may hold perspectives, goals, or assumptions that differ from the principles of maqasid syaria. The study employed the content analysis method, a systematic approach to examining the fundamental aspects of the material under investigation, specifically literature on good governance and maqashid syaria, as initiated by Nurcholish Madjid. The study's findings reveal three main points. Firstly, Nurcholish Madjid emerges as a highly influential contemporary figure within Islam, particularly in Indonesia during the 20th-century transition period. His ideas underscore the necessity of renewing Islam in line with societal demands and contemporary knowledge. His philosophy emphasizes the elevation of human dignity, equality, religious freedom, and social maturity when confronting diversity. Secondly, the compatibility between the maqashid syaria and Nurcholish Madjid's ideologies stems from their shared sources—the Qur'an and Hadith. This relationship is further bolstered by the Qawa'id fiqhiyyah approach, which establishes principles of effective governance. Lastly, Nurcholish Madjid's principle of good governance is grounded in the principle of tawhid and resonates with the maqashid syaria (syaria objectives) framework, particularly concerning muhafadah al-din. Notably, the tawhid principle, concerning the types of maqashid syaria al-Syatibi, falls within the daruriyyah (fundamental) category. Conversely, the hajiyyah level comprises the supportive principles.